Modeling the response of flexible risers in the Quasi-steady regime (2010)
ABSTRACT: Several research efforts have been directed toward the development of models for response prediction of flexible risers. The main difficulties arise from the fact that the dynamic response of flexible risers involves highly nonlinear behavior and a self-regulated process. This article presents a quasi-steady approach for response prediction of oscillating flexible risers. Amplitude-dependent lift coefficients are considered, as is an increased mean drag coefficient model during synchronization events. Experimental validation of the proposed model was carried out using a 20-m riser model excited by forced harmonic vibration at its top end. Large variations in the hydrodynamic force coefficients, a low mass ratio value, and synchronization events are the main features of the model presented in this article. Experimental validation was provided for the asymmetric, transverse, diagonal, and third vortex regimes.